The interplay among SRL strategies, English self-efficacy, and English proficiency of Thai university students - Aisah Apridayani; Adisa Teo (Universitas Syiah Kuala, 2021)
This study examined the interplay among self-regulated learning (SRL) strategies, English self-efficacy, and English proficiency of EFL students at the university level in Thailand. The data collection instruments comprised the Self-Regulated Learning Strategies Questionnaire (SRLSQ), English Self-Efficacy Questionnaire (ESEQ), and a standardized English proficiency test. It involved 215 first-year non-English major students through purposive and random sampling methods. The collected data were examined by using descriptive statistics, Pearson’s correlation, and multiple-linear regression analyses. The results disclosed that lower-level Thai EFL students – A1 and A2 had a high use of SRL strategies. However, for higher proficiency levels – B1 and B2, it was only B2 students who reported high use of SRL strategies. B1 students reported that they only employed SRL strategies moderately. Moreover, higher proficiency students had higher levels of English self-efficacy than those with lower proficiency levels. A direct influence was observed between students’ use of SRL strategies and their English proficiency levels, yet self-efficacy only possessed an indirect effect. This study proposes some practical ideas to integrate SRL strategies into the English curriculum and instructions and enhance Thai EFL students’ English self-efficacy.